Transcriptome analysis revealed that AcWRKY75 transcription factor reduced the resistance of kiwifruit to Pseudomonas syringae pv. actinidiae - Ye, Lixia; Luo, Minmin; Wang, Yafang; Yu, Mengqi; Wang, Zhi; Bai, Fuxi; Luo, Xuan; Li, Li; Huang, Qiong; Peng, Jue; Chen, Qi; Chen, Qinghong; et al. (Frontiers in Plant Science, 2024)
The kiwifruit canker disease caused by Pseudomonas syringae pv. Actinidiae actinidiae (Psa) seriously threatens the development of kiwifruit industry. So far, only a limited number of Psa-resistant kiwifruit varieties have been identified, and the underlying molecular mechanisms are still largely unknown. In this study, we evaluated the Psa resistance of six hybrid populations and screened a resistant segregation population R1F2. Then, transcriptome analysis on the Psa extremely high-resistant (HR) and extremely high-susceptible (HS) plants of the R1F2 population was performed. KEGG enrichment analysis revealed that differentially expressed genes (DEGs) were significantly enriched in plant hormone signal transduction pathways, including auxin, abscisic acid, zeatin, jasmonic acid and salicylic acid. Furthermore, several transcription factors (TFs), especially WRKY TFs, were identified among the DEGs.The qRT-PCR showed that AcWRKY75 was highly expressed in the HS plants.Additionally, AcWRKY75 was significantly induced in the HS cultivar 'Hongyang' after Psa inoculation. Sequence amplification analysis showed that there was polymorphism in the DNA sequence of AcWRKY75 gene, but no HR or HS-specific differences were observed. Subcellular localization and transcriptional activity analysis confirmed that AcWRKY75 functions as a nucleus-located transcriptional activator. Transient overexpression of AcWRKY75 in kiwifruit leaves reduced the resistance to Psa, while silencing AcWRKY75 by virus-induced gene silencing (VIGS) slightly enhanced the resistance to Psa. Furthermore, AcWRKY75 exhibited a weak interaction with the promoter of the ABA-related DEG AcBet V1 (Acc27163). Our findings elucidated that AcWRKY75 may negatively regulate the Psa resistance of kiwifruit through the hormone signaling pathway, which laid a foundation for the analysis of the disease resistance mechanism of kiwifruit canker.